Exploring the Potential of (Chrysophyllum-Albidum) Udara Seed Extract as a Natural Corrosion Inhibitor For Mild Steel - Nnadikwe Johnson; Iheme Chigozie; Chinemerem Joy Johnson; Ibe Raymond Obinna; Mbadike Columbus Asodike (Jurnal Teknik Indonesia, 2025)
Mild steels composed by two main elements, they are iron (Fe) and carbon (C) elements which is  widely used in industry  because of its resistance and more affordable in terms of cost  than stainless steel, but their weakness is that they have low corrosion resistance. One way to modify mild steel is by coating them with antioxidant compounds that can delay, slow down, and prevent lipid oxidation process, which is obtained from(Chrysophyllum-Albidum) Udara seed extract. This research work is aimed at producing organic corrosion inhibitor from(Chrysophyllum-Albidum) Udara seed extract. Also, to utilize this organic corrosion inhibitor as a substitute for chemical corrosion inhibitors which contain toxic compounds, and determining the corrosion inhibition efficiency of the Udara seed extract in Hydrochloric acid medium. This was carried out by weighing the mild steel pieces. Udara seed extract was also weighed and added into each of the transparent glass bottles that was used in the experiment. However,  10.0g Udara seed powder was added into bottle 1 containing 0.5m of the dilute tetraoxosulphate (vi) acid. 20.0g to bottle 2, containing the same concentration of the  acid.  30.0g to bottle 3, 40.0g to bottle 4, containing 0.5m of the dilute tetraoxosulphate (vi) acid. And 50.0g to bottle 5 containing the same acid, and Finally, bottle 6 was containing the mild steel metal and the dilute tetraoxosulphate (vi) acid. It was observed that the Udara seed extract effectively inhibited mild steel corrosion in H2SO4 solution. Inhibition efficiency was observed to improve with increase in concentration of the extract. It was generally observed that inhibition efficiency was low at the first hour and with the blank and the first concentration and gradually increases by the preceding hours and concentrations. Weight loss increased with increase in time portraying retardation in the inhibitor efficiency with increase in time.